Impact of Vulnerable Group Development (VGD) program on Improvement of Woman Headed Household Consumption Diversity in Bangladesh - Pradhan, Mohammad Abdul Hannan; Sulaiman, Jamalludin (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
A number of studies have established that Vulnerable Group Development (VGD) program beneficiaries are better off during the two-year benefit cycle. This study was an attempt to provide evidence using household survey data on whether the VGD program improves beneficiary household welfare over the cycle. This study was conducted in Sylhet district of Bangladesh. A structured questionnaire was administered to collect data from equal number of beneficiary and non-beneficiary households. This study used the propensity score matching (PSM) method to analyse data. The study finds a robust and positive effect of program on the beneficiary households to improve their wellbeing through improving meal frequency, per capita expenditure. The results signify consumption variability of the beneficiarieshouseholds. Furthermore, this behaviour of beneficiaries increases the demand for different items of good at the local market which could help enhancing the national growth. Thus the number of program beneficiary could be increased to promote the process.